Challenges Facing Small and Medium Enterprises in Singapore Seeking Access to International Markets - Wan, Hong Jim (Digital Repository of Theses, 2024)
According to The World Bank, the GDP in Singapore was ranked 36th in the world at 364 billion US dollars in 2019 while GDP per capita was ranked 10th in the world at 65 thousand US dollars in 2019. According to the Singapore Department of Statistics for 2020, small and medium enterprises (SMEs) in Singapore support 70% of total employment while contributing to 43% of the national GDP. Given Singapore’s small size, it is not surprising that its domestic market is limited. For Singapore SMEs who are ambitious for further growth, the only way to grow is to go overseas. Enterprise Singapore conducted a survey in 2016 and found that for SMEs with businesses in foreign markets, their overseas revenues are higher than their domestic revenues. However, encouraging Singapore SMEs to move into international markets has proven to be not easy. Singapore SMEs are reluctant to venture overseas and will continue to be domestically focused. Not enough of them are willing to leave their comfort zone and expand their presence into international markets. As reported in The Straits Times, the national newspaper, on 29 January 2018, a survey done by QBE Insurance on more than 400 firms discovered that only fourteen per cent of the SMEs surveyed express intention to expand outside the shores of Singapore. Nearly 50 per cent simply showed no interest in going overseas for the near future. Among other reasons for not intending to access international markets, 42 per cent was due to insufficient funds, while 38 per cent felt that they are still unfamiliar with the standards and processes of the overseas markets. However, the pressing for entrepreneurship awareness has become more evident in recent years. Maintaining a double-digit GDP Growth Rate in Singapore or even to achieve between 5 to 10 percent has become more challenging. With a GDP Growth Rate of 13.94% in 1970, it has been less than 5% from 2012. Prior to the Covid-19 pandemic, GDP for 2019 ended at a 1.35% increase from previous year. Yet, Singapore’s Foreign Direct Investment (FDI) has been increasing since the nation’s independence. FDI for 2019 closed at US$120.44 billion, contributing to 32.17% of the nation’s GDP. Singapore ranked second in the world for its FDI in 2019, second only to the United States. This research project will thus study and present a thorough review of the constraints faced towards entering entrepreneurship in Singapore, identifying the obstacles, concerns and economic challenges faced. Subsequently, the constraints, concerns and economic challenges faced by Singapore SMEs when accessing international markets will be identified. Finally, this research project will establish proposals, changes and recommendations pertaining towards encouraging entrepreneurship into the Singapore population as well as facilitating more SMEs in Singapore to expand into neighbouring countries and beyond. The results of the study and learnings taken will hopefully help to encourage more entrepreneurs coming from within the Singapore population as well as more Singapore SMEs to boldly move out of the comfort of Singapore and expand overseas.